Studies of Some Properties and the Structure of Polyethylene Glycol (PEG) Macromolecules Adsorbed on a TiO Surface - S. Chibowski; M. Paszkiewicz (Adsorption Science & Technology)
In the studies presented, the influence of the molecular weight of polyethylene glycol (PEG) on the adsorption and electrical properties at the metal oxide/polymer solution interface has been determined. The main factors responsible for the observed changes in the zeta potential and surface charge of titania were determined on the basis of the data obtained. It was demonstrated that changes in the ionic structure of the Stern layer depend on the molecular weight of PEG and its conformation. A possible mechanism for the changes in zeta potential both with pH and molecular weight was proposed on the basis of values of the surface charge difference (Δσ 0 ) and the diffuse layer charge difference (Δσ d ) as determined in the presence and absence of the polymer. The thickness of the adsorption layer (δ) on the surface of titania was calculated from the zeta potential changes, both in the presence and absence of the polymer. A distinct influence of the PEG molecular weight was noted on the values of the adsorption layer thickness (δ) determined. The structures of the macromolecules in solution and at the solid/solution interface were compared and from the dependencies obtained some changes in the shape and dimensions of the polymer coils on passing from the bulk solution to the interface were proposed.